Clearing Mechanism in Sharia Banking According to Al-Ghozali and Muhammad Nejatullah Siddiqi Thoughts - Bustanul Arifin (Jurnal Mahkamah : Kajian Ilmu Hukum Dan Hukum Islam, 2021)
This research intended to look at the clearing mechanism in the viewpoint of classical and contemporary Islamic thought that in Islamic law the clearing is identical to term “wakalah” (granting power of attorney) because in wakalah, the customer authorized the bank to represent himself to perform certain service work with various mechanisms stated in the Regulation of Bank Indonesia. An important issue in this paper contained philosophical aspects of the clearing application in sharia banking. This research was reviewed by qualitative method with library research with philosophical approach. The results obtained as follows: The thoughts of Al-Ghozali and Muhammad Najetullah As-Shiddiqy were said to be relevant to the clearing mechanisms in sharia banking today. With the maslahah (welfare) concept of Al-Ghozali, which was the core of some of the five basic objectives (religion, life, response/reason, descendants and property). The concept of maslahah (welfare) for the community welfare, the clearing mechanism used in conventional banks can be used in Sharia banking by having wakalah agreement. While the neoclassical approach (a combination of the new model and the classic model), Muhammad Najetulloh As-Shiddiqy, in which although there was a new method, he still used the old method without erasing all the results of the analysis of the previous figures. Therefore, this approach can also be said to be relevant to the clearing mechanism in sharia banking.